Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004210.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to prevent hypothermia at birth in preterm and/or low birthweight babies

Abstract: Plastic wraps or bags, skin-to-skin care and transwarmer mattresses all keep preterm infants warmer, leading to higher temperatures on admission to neonatal units and less hypothermia. Given the low NNT, consideration should be given to using these interventions in the delivery suite. However, the small numbers of infants and studies and the absence of long term follow-up mean that firm recommendations for clinical practice cannot be given. There is a need to conduct large, high quality randomised controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 69 publications
0
24
0
1
Order By: Relevance
“…A Cochrane review [305] concluded use of plastic wraps or bags, transwarmer mattresses, and early skin-to-skin contact, all kept preterm and/or low birth weight babies warmer compared to routine thermal care. Another Cochrane review compared incubators with radiant heaters in preterm babies [306], showing no differences in severe infections or deaths, although radiant heaters were associated with greater water loss.…”
Section: Resultsmentioning
confidence: 99%
“…A Cochrane review [305] concluded use of plastic wraps or bags, transwarmer mattresses, and early skin-to-skin contact, all kept preterm and/or low birth weight babies warmer compared to routine thermal care. Another Cochrane review compared incubators with radiant heaters in preterm babies [306], showing no differences in severe infections or deaths, although radiant heaters were associated with greater water loss.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have shown that despite these measures many preterm babies are cold on arrival in the neonatal unit 11 12. The use in recent years of polyethylene occlusive skin wraps or plastic bags is effective in reducing TEWL30 and, in babies under 28 weeks' gestation, results in higher temperatures on admission 31 32…”
Section: Options For Achieving These Goalsmentioning
confidence: 99%
“…Warming is of vital importance as neonates have a low percentage of body fat and are at high risk of hypothermia. All EDs should possess a warming device as hypothermia incurred during postnatal resuscitation is associated with significant morbidity and mortality 7. The availability was particularly limited in EDs catering for adults only: only 57% of adult-only EDs had a source of warmth compared with 100% of children-only EDs.…”
Section: Discussionmentioning
confidence: 99%